Comparative Efficacy of Root Repair versus Partial Meniscectomy and Observation for Patients with Meniscus Root Tears - Dai, Wenli; Yan, Wenqiang; Leng, Xi; Wang, Junyan; Hu, Xiaoqing; Ao, Yingfang (The Journal of Knee Surgery, 2021)
The purpose of this study was to (1) compare the efficacy of root repair versus partial meniscectomy and observation for patients with meniscus root tears; (2) compare osteoarthritis (OA) progression and functional outcomes in patients with isolated repair and with adjuvant surgery; and (3) evaluate OA progression and functional outcomes after pullout repair or all-inside repair of meniscus root tears. We performed a systematic literature search in PubMed, Embase, Scopus, and the Cochrane Library up to September 1, 2020, to identify studies that evaluated the efficacy of root repair versus partial meniscectomy and observation in patients with meniscus root tears. Random-effects meta-analysis was used to pool data. A total of nine studies were included in the meta-analysis, with 485 patients comprising 238 in the root repair group, 113 in the partial meniscectomy group, and 134 in the observation group. The mean age of the patients ranged from 46.1 to 64.8 years. Compared with partial meniscectomy, root repair was associated with significantly lower postoperative Kellgren–Lawrence (K-L) grade (mean difference [MD]: −0.62, 95% confidence interval [CI]: −1.00 to −0.23) and progression to arthroplasty rate (odds ratio [OR]: 0.15, 95% CI: 0.04–0.60) at final follow-up. Compared with observation, root repair was associated with significantly lower arthroplasty rate (OR: 0.07, 95% CI: 0.01–0.44) and better International Knee Documentation Committee (IKDC) score (MD: 8.07, 95% CI: 0.72–15.41) at final follow-up. Moreover, significantly lower postoperative K-L grade and progression to arthroplasty rate, as well as higher IKDC and Lysholm scores were seen in favor of root repair in patients with isolated meniscus root tears. Additionally, significantly lower OA progression and higher function scores were found in favor of root repair when the tears were repaired with pullout technique. Current evidence indicates that root repair with pullout technique may be a better choice than partial meniscectomy and observation for patients with isolated meniscus root tears as measured by OA progression, progression to arthroplasty, as well as functional outcomes.
Keywords: meniscus root tears; root repair; partial meniscectomy; observation; osteoarthritis